Nigeria Centre for Disease Control, awareness creation and risk communication of Covid‑19 pandemic amongst non‑literate population in South‑West Nigeria: Lessons for future health campaign - Rachael Ojeka-John; Bernice O. Sanusi; Omowale T. Adelabu; Felix O. Talabi; Isaac A. Oyekola; Olanrewaju O.P. Ajakaiye; Ejem A. Ejem (AOSIS, 2023)
Risk communication of Covid‑19 pandemic in Nigeria appeared to be urban‑centered with the dominant use of social media, print communication and other controlled media. In such times of public health emergencies, non‑literate population could be vulnerable as a result of their limited understanding of the nature of such health risk. Therefore, the study seeks to investigate the extent to which Nigeria Centre for Disease Control (NCDC) communicated the risk of Covid‑19 disease to non‑literate population in its public health campaign during the pandemic in South‑West Nigeria. The study adopts risk communication theory which advances the approach communication should take during public health emergencies. Using descriptive cross‑sectional mixed methods research design, a sample of 420 respondents were purposively selected from 6 towns in the rural areas of Lagos, Oyo and Osun states to examine the level of awareness on Covid‑19 pandemic among non‑literates. In addition, NCDC risk communication on Covid‑19 for non‑literate population were analyzed from 3 Jingles in Yoruba language as well as 9 flyers designed for Covid‑19 disease from NCDC websites. Results showed that NCDC awareness creation on Covid‑19 disease for non‑literates in Southwest achieved significant success as a result of the medium used in creating awareness. Specifically, radio was highly rated among majority of the respondents (60.4%) followed by health workers (19.8%) as channels that created understandable message on Covid‑19 safety protocols.Further findings on Jingles content revealed that all Covid‑19 safety protocols were communicated in Yoruba language for Southwest populace. However, NCDC fall short in communi‑ cating Covid‑19 risk effectively for non‑literates in Southwest as jingles only buttressed the Covid‑19 safety protocols and symptoms as well as the need to comply, without educating the masses on the dreadful nature of the disease and its dynamics. Though flyers designed by the NCDC communicated risk to an extent, nevertheless, graphics and symbols on Covid‑19 disease were complimented by words in English language only, which could be difficult for non‑literates to decipher. Based on the findings, the study recommends that public health agencies need to educate non‑literate population about the nature of a disease more than creating awareness about the outbreak of a disease, and such education should be strategic, context‑specific, and evidence‑based.